Estudo da conexão de um filtro híbrido back-to-back aplicado em laminador de tiras a quente com cicloconversores - Krause, Rafael Cabral Knaip (2023)
This work consists of a detailed analysis of the connection of a hybrid filter back-to-back between an active and passive filter in a hot strip mill (HSM) with cycloconverters, located in a steel mill in the region of Grande Vit´oria. Through simulations, an evaluation of the performance of the hybrid back-to-back filter in harmonic compensation and damping of the harmonic resonance present in the system was performed. In addition, the study also investigated the reduction of the current overload in the branches of the passive filtering system, in face of a load expansion in the HSM. The results obtained evidenced that the hybrid filter topology back-to-back allowed to significantly improve the Power Quality (PQ) and eliminate the overload in the pre-existing passive filtering branches in the electrical system of the LTQ. This improvement was achieved by implementing active filters of low rated capacity, when compared to the load of the LTQ electrical system. These findings demonstrate the effectiveness of the hybrid back-to-back filter in improving the QEE and balancing the operation of the HSM. Furthermore, it is emphasized that these findings have relevant implications for steel mills with similar characteristics around the world, reinforcing the importance of this technology as a viable solution for reducing harmonic components and resonances in large industrial electrical systems.